2015
DOI: 10.1186/s12888-015-0620-9
|View full text |Cite
|
Sign up to set email alerts
|

Triage, decision-making and follow-up of patients referred to a UK forensic service: validation of the DUNDRUM toolkit

Abstract: BackgroundForensic medium secure services in the UK are a scarce but essential resource providing care for those in the criminal justice system with severe mental disorder. Appropriate allocation of beds to those most in need is essential to ensure efficient use of this resource. To improve decision-making processes in a UK forensic service, an admissions panel utilized the DUNDRUM 1&2 (D1 & D2) triage instruments.MethodsDemographic, diagnostic and clinical information on a prospective sample of referrals to a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
41
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(44 citation statements)
references
References 18 publications
2
41
1
Order By: Relevance
“…Validation studies have shown good psychometric qualities (Flynn, O'Neill, McInerney, & Kennedy, 2011;Freestone et al, 2015;O'Dwyer et al, 2011) and indicated that the DUNDRUM-1 items can predict the level of therapeutic security needed (Flynn et al, 2011;Freestone et al, 2015) and LOS (Davoren et al, 2015) while the DUNDRUM-3 and DUNDRUM-4 can predict moves between levels of therapeutic security (Davoren et al, 2012) and discharge (Davoren et al, 2013).…”
Section: Dangerousness Understanding Recovery and Urgency Manual (Thmentioning
confidence: 99%
“…Validation studies have shown good psychometric qualities (Flynn, O'Neill, McInerney, & Kennedy, 2011;Freestone et al, 2015;O'Dwyer et al, 2011) and indicated that the DUNDRUM-1 items can predict the level of therapeutic security needed (Flynn et al, 2011;Freestone et al, 2015) and LOS (Davoren et al, 2015) while the DUNDRUM-3 and DUNDRUM-4 can predict moves between levels of therapeutic security (Davoren et al, 2012) and discharge (Davoren et al, 2013).…”
Section: Dangerousness Understanding Recovery and Urgency Manual (Thmentioning
confidence: 99%
“…In this study we found the scores on the DUNDRUM tool were closely aligned to the decisions of both the Broadmoor admission panel and the assessing clinicians. 9,10,15 This demonstrated the strong clinical relevance of the tool. The DUNDRUM tool is designed to support clinical decision-making regarding triaging admissions, but it does not replace clinical decision-making.…”
Section: Discussionmentioning
confidence: 73%
“…The DUNDRUM tools have been validated in forensic mental health hospital settings and prison settings in multiple jurisdictions and have excellent psychometric properties. 9,[14][15][16][17] The DUNDRUM-1 triage security scale has been shown to have good internal consistency (Cronbach's alpha 0.95 in a Dundrum sample validation and 0.77 in an international validation study) and good interrater reliability. 9,10,[15][16][17][18][19] Interrater reliability is better following training.…”
Section: Needs Assessment Tool For Secure Carementioning
confidence: 99%
“…20 They rate the level of security a patient should be admitted to and the urgency of need for admission; has good psychometric properties and has been internationally validated. [21][22][23][24][25][26][27] The DUNDRUM-3 programme completion and DUNDRUM-4 recovery scales were used in this study. These tools rate the successful completion of therapeutic programmes by the patients, and rate the patient's overall recovery in a holistic manner, respectively.…”
Section: Assessing Risk and Needsmentioning
confidence: 99%